2015
DOI: 10.1016/j.jad.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to, and searching for, information about suicide and self-harm on the Internet: Prevalence and predictors in a population based cohort of young adults

Abstract: BackgroundThere is concern over the potential impact of the Internet on self-harm and suicidal behaviour, particularly in young people. However, little is known about the prevalence and patterns of suicide/self-harm related Internet use in the general population.MethodsCross sectional study of 3946 of the 8525 participants in the Avon Longitudinal Study of Parents and Children (ALSPAC) who were sent a self-report questionnaire including questions on suicide/self-harm related Internet use and self-harm history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 37 publications
3
94
0
9
Order By: Relevance
“…Specific countries have taken steps to legally ban or block websites discussing practical aspects of suicide (Biddle, Donovan, Hawton, Kapur, & Gunnell, 2008). An additional consideration is that positive effects of the Internet have been documented, including the offering of help and social support (Mars et al, 2015). This area of research is still emerging and requires greater and more rigorous study.…”
Section: Environmental Risk Factors and Correlatesmentioning
confidence: 99%
“…Specific countries have taken steps to legally ban or block websites discussing practical aspects of suicide (Biddle, Donovan, Hawton, Kapur, & Gunnell, 2008). An additional consideration is that positive effects of the Internet have been documented, including the offering of help and social support (Mars et al, 2015). This area of research is still emerging and requires greater and more rigorous study.…”
Section: Environmental Risk Factors and Correlatesmentioning
confidence: 99%
“…Consider the Wikipedia article "Suicide and Internet" which features the following statement, "A survey has found that suicide-risk individuals who went online for suicide-related purposes, compared with online users who did not, reported greater suicide-risk symptoms, were less likely to seek help and perceived less social support," highlighting a report by Harris, McLean, and Sheffield [10] . As identified by scite [11] , this report was later contradicted by a subsequent study finding that suicide-related Internet use individuals were more likely to seek help [12] (Figure 3). Providing contextual citation information for this Wikipedia article could influence behavioral choices that have potentially life or death consequences for a large population of people.…”
mentioning
confidence: 80%
“…Harmful content such as suicide coaching is abundant on the Internet [43]. Access to suicide promotion or self-harm websites is widespread [44]. Moreover, susceptible consumers may eventually become content "creators," posting their own self-mutilation videos or images.…”
Section: Harmful Contentmentioning
confidence: 99%